CALL FOR AN IMPROVED SET OF DECAY CONSTANTS FOR GEOCHRONOLOGICAL USE - Begemann F.; Ludwig K.R.; Lugmair G.W.; Min K.; Nyquist L.E.; Patchett P.J.; Renne P.R.; Shih C.Y.; Villa I.M.; Walker R.J. (My University, 2001)
The accuracy of radioisotopic ages is, at present, limited by the accuracy of radioactive decay constants. A literature survey reveals that decay constants used in geo- and cosmochronology usually are assigned uncertainties of ca. 1% but that there are very much larger unaccounted discrepancies between decay constants reported by different ''counting groups'' as well as differences between results derived from counting experiments and from the comparison of ages obtained on the same samples by utilizing different radioactive clocks. An extension and partial revision of the decay constants recommended in 1976 for adoption in geo- and cosmochronology by the International Union of Geological Sciences (IUGS) appears both desirable and feasible, given the analytical improvements of the last 20 years. We call for a concerted effort to achieve improvements in the near future. For this it will be necessary to rigorously evaluate counting biases in counting determinations, initial daughter contamination for ingrowth experiments, and the existence of truly ''point-like'' geological events for age comparison approaches.